Factors affecting students' persistence to enrol in STEM education / Nurul Yasmin Nor Huzir ... [et al.] - Nor Huzir, Nurul Yasmin; Ahmad, Noraini; Hassanuddin, Nor Aini; Yusoff, Sarah; Rosly, Nur Syazana (Universiti Teknologi MARA, 2025)
Science, technology, engineering, and mathematics (STEM) education is vital in producing a highly skilled and knowledgeable Malaysian workforce to meet the demand for its industries. Malaysia aims to be a developed country that initiates the technology itself instead of just being a user. Despite this ambitious goal, STEM education in Malaysia faces challenges due to low enrolment in STEM elective subjects. This declining trend is transparent in secondary school since students are given a choice to enrol in STEM education or any other stream provided. While STEM elective subjects are viewed as tough and difficult, there is a tendency that students may decide to change to another stream after they have enrolled in STEM education. Due to this, the study focused on what factors may contribute to students’ persistence in continuing to enrol in STEM education until they finish secondary school. Therefore, this study has specified three factors to be studied, which are self-efficacy, socioeconomic status (SES), and students’ academic achievement towards their persistence to enrol in STEM education. Form 4 students who took STEM elective subjects in Sekolah Menengah Kebangsaan (SMK) Dang Anum have been selected as the population understudied, and 80 respondents were selected to answer a series of questionnaires that comprised 40 questions in total. All the data was collected within a one-week time frame and further analyses through the statistical software Statistical Package for Social Science (SPSS) by using Spearman’s correlation test to find the correlation between each independent variable and the dependent variable under study. It was found that there is a positive relationship between self-efficacy, socioeconomic status (SES), academic achievement, and students’ persistence to enrol in STEM education